Employment status and personal characteristics in patients awaiting hip-replacement surgery - Bohm, Eric R. (Canadian Medical Association, 2009)
BACKGROUND: Total hip arthroplasty (THA) is a cost-effective surgical intervention that substantially improves quality of life. Recent advances have broadened the indications to include younger, working-age patients. Despite these benefits, there are often long waits for this procedure in Canada. Furthermore, there exists little documentation of the ability of patients waiting for THA to maintain employment or perform their occupational duties. METHODS: I prospectively identified patients younger than 65 years from a primary hip-replacement surgery waiting list. The study coordinator contacted patients by phone and asked them to participate; if they agreed, we mailed them a validated questionnaire. To compare working with nonworking patients, I used univariate analysis and logistic regression modeling. RESULTS: A total of 84 of the 100 patients who agreed to participate returned the questionnaire. While awaiting THA, 20% of patients who considered themselves to be in the workforce were off work owing to their hip conditions. Work cessation resulted in a median drop in income of $15 000 CDN and forgone tax revenues of $3800. Poor hip function was related to both lowered productivity and work cessation before surgery. Patients with an Oxford 12 hip score of 50 or worse appeared to have about a 50% chance of stopping work before THA, whereas those with a score of 40 or better appeared to have only a 10% chance of stopping work. CONCLUSION: About 20% of patients in the workforce who are awaiting THA are off work owing to their hip conditions while on the waiting list. Poor hip function is associated with work cessation and decreased productivity.